VD_FINDINFO Pron / 2012 / 28 vom 14. Februar 2012 - VD Tribunal cantonal (2012)
TRANSACTION JUDICIAIRE, TRANSACTIONACCORD, FRAIS JUDICIAIRES, MESURE PROVISIONNELLE | 241 al. 1 CPC (CH), 241 al. 2 CPC (CH), 241 al. 3 CPC (CH), 241 CPC (CH)